Factors affecting the adoption of digital payment systems - Giri, Sushant Raj; Ghimire, Subodh Kumar (Journal of Innovations in Engineering Education, 2020)
Payment for goods and services in Nepal is characterized by long queues; long distance traveling and time wasting that generally affect business activities and ultimately economic development. Settling utility bills, payment for goods and services, and money transfers has been a major headache for individual and firms in Nepal resulting in declined business activities and huge debt to most of the utility providers. In fact, the country have not yet realize the full benefits of the technological advances in electronic payment such as the use of cards, automated teller machines (ATM), the Internet, mobile phones, and other devices. To identify factors that influence the acceptance of these payment systems a theoretical extension of the Technology Acceptance Model, Theory of Planned Behaviour and Trust was used to evaluate the factors that influence the adoption and acceptance of the information technology and system of Internet; in the e-Finance sector in Nepal, especially in digital transaction services. This study will address the questions about the factors that affect the adoption of digital transaction services and the extent these factors affect people’s intention towards the adoption of those services.